Membangun Karakter Santri Melalui Pendekatan Spiritual Berbasis Al-Quran dan Hadits: Studi Empiris di Lingkungan Pesantren Raudlatul Hasaniyah Mojolegi Gading Probolinggo - Saifullah Saifullah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the role of a spiritual approach based on the Quran and Hadith in shaping the character of students (santri) at Pesantren Raudlatul Hasaniyah Mojolegi Gading Probolinggo. A qualitative approach using a case study method was employed to analyze activities such as the Ngaji of the Riyadussholihin book, congregational Tahajjud prayer, and congregational Dhuha prayer. The findings indicate that these religious activities have a positive impact on the character development of the santri. The Ngaji of the Riyadussholihin book deepens religious and ethical understanding, while the Tahajjud and Dhuha prayers teach discipline, steadfastness, and gratitude. Overall, the implementation of a spiritual approach based on the teachings of the Quran and Hadith has successfully contributed to the formation of santri with improved character, noble morals, and readiness to face life's challenges. This study emphasizes the importance of religious education in the holistic development of character, including spiritual, moral, and social aspects.